Strategies for Enhancing Supply Chain Efficiency in the Agricultural Sector Through the Implementation of the SCOR Racetrack Method - Khoerun Nisa Safitri; Asrul Fole; Nurul Aini; Palmadi Putri Surya Negara (Agroindustrial Technology Journal, 2025)
Supply chain efficiency in the agricultural sector is a key factor in enhancing productivity and competitiveness. This study aims to analyze strategies for improving supply chain efficiency through the implementation of the SCOR Racetrack method using a quantitative and descriptive approach. Data were collected through surveys and interviews with 150 respondents, consisting of farmers, distributors, and retailers in several agricultural regions in Indonesia. The analysis was conducted using Quantitative Method with Descriptive and Analytical Design methods and supply chain efficiency. The results indicate that the SCOR Racetrack method can improve operational efficiency by 30%, reduce delivery cycle time by 25%, and increase customer satisfaction by up to 40%. The implementation of digital technology in the supply chain contributes to an efficiency increase of 50.9%, while logistics costs decreased by 28% and product damage rates were reduced by 41.6%. Regional analysis shows that South Sulawesi exhibits the highest efficiency level, while West Sumatra still faces challenges in distribution optimization. Key factors influencing the success of implementation include collaboration among stakeholders, adoption of information technology, and enhancement of human resource capabilities. Thus, this study emphasizes that the SCOR Racetrack method can serve as a strategic solution in building a more efficient, sustainable, and competitive agricultural supply chain. Recommendations for future research include the development of an adaptive model based on artificial intelligence to improve demand forecasting and inventory management in the agricultural sector.